PENGARUH PROFITABILITAS, LIABILITAS, LEVERAGE, PERTUMBUHAN PENJUALAN, DAN DIVIDEN TERHADAP HARGA SAHAM (KONSISTEN TERDAFTAR LQ45 PERIODE TAHUN 2014-2016) - Meitry Dina Wisma Dewi; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2019)
This study aims to analyze the effect of profitability on LQ 45 Index Stock Price, analyze the effect of liquidity on the LQ 45 Index Stock Price, analyze the influence of Leverage on the LQ 45 Index Stock Price, analyze the effect of sales growth on the LQ 45 Index Stock Price, analyze the effect of dividends on LQ 45 Index Stock Price.The population in this study is the LQ45 company listed on the IDX. While the sample in this study uses LQ45 companies that are consistently listed on the Stock Exchange in 2014 to 2016. Sampling in this study uses purposive sampling. Data analysis techniques use multiple regression analysis with classical assumptions.Based on the results of the analysis in the previous section, the following conclusions can be drawn: Profitability affects stock prices, Liquidity does not affect stock prices, Leverage does not affect stock prices, Sales growth affects stock prices, Dividends affect stock prices.